A constitutive model for fiber kinking: Formulation, finite element implementation, and verification. (February 2020) - Bergan, Andrew C.; Herráez, Miguel; González, Carlos; Lopes, Cláudio S.
Abstract: A new mesoscale material model is proposed to analyze structures that fail by the fiber kinking damage mode. The model is formulated following the fiber kinking theory such that the interaction of shear nonlinearity and fiber rotation are tracked throughout the loading history. The model is implemented as a user-defined material in a commercial finite element code. A decomposition algorithm is introduced in the finite element implementation to decouple the mesh size and kink band width. To evaluate the assumptions of the mesoscale model, the results were compared with those of a high-fidelity micromechanical model. A direct comparison between the two models shows remarkable correlation, providing evidence that the key features of the fiber kinking phenomenon are appropriately accounted for in the mesoscale model. The model is demonstrated for a simple unnotched compression configuration. The results show that the model is successful at representing the kinematics of fiber kinking.